Numerical Study of Divergence Cleaning and Coronal Heating/Acceleration Methods in the 3D COIN-TVD MHD Model - Liu, Chang; Shen, Fang; Liu, Yousheng; Zhang, Man; Liu, Xiaojing (Frontiers in Physics, 2021)
In the solar coronal numerical simulation, the coronal heating/acceleration and the magnetic divergence cleaning techniques are very important. The Coronal Interplanetary-Total Variation Diminishing (COIN-TVD) magnetohydrodynamic (MHD) model is developed in recent years that can effectively realize the coronal-interplanetary three-dimensional (3D) solar wind simulation. In this paper, we focus on the 3D coronal solar wind simulation by using the COIN-TVD MHD model. In order to simulate the heating and acceleration of solar wind in coronal region, the volume heating term in the model is improved efficiently. Then, the influence of the different methods to reduce the ∇⋅B constrain error on the coronal solar wind structure is discussed. Here, we choose Carrington Rotation (CR) 2199 as a study case, and try to make a comparison of the simulation results among the different magnetic divergence cleaning methods, including the diffusive method, the Powell method and the composite diffusive/Powell method, by using 3D COIN-TVD MHD model. Our simulation results show that with the different magnetic divergence cleaning methods, the error can be reduced in different levels during the solar wind simulation. Among the three divergence cleaning methods we used, the composite diffusive/Powell method can maintain divergence cleaning constraint better to a certain extent, and the relative magnetic field divergence error can be controlled at the order of 10^-9. Although these numerical simulations are performed for the background solar corona, these methods are also suitable for the simulation of CME initiation and propagation.